Ion-assisted gate recess process induced damage in GaN channel of AlGaN/GaN Schottky barrier diodes studied by deep level transient spectroscopy. (24th January 2017) - Ferrandis, Philippe; Charles, Matthew; Baines, Yannick; Buckley, Julien; Garnier, Gennie; Gillot, Charlotte; Reimbold, Gilles
Abstract: Deep traps in AlGaN/GaN Schottky barrier diodes have been investigated using deep level transient spectroscopy. It has been found that ion-assisted gate recess process leads to the formation of electron traps. The defects related to these traps are mainly located in the two-dimensional electron gas channel below the Schottky contact, meaning that the partial etching of the AlGaN layer produces damage on the top of the underlying GaN layer. The activation energies of the electron traps, extracted from the data, range between 0.28 and 0.41 eV. We believe that these centers are complexes linked with nitrogen vacancies which may behave as extended defects.